Migration of red‐backed shrikes from the Iberian Peninsula: optimal or sub‐optimal detour?. (January 2017) - Tøttrup, Anders P.; Pedersen, Lykke; Onrubia, Alejandro; Klaassen, Raymond H. G.; Thorup, Kasper
Abstract : The current Northern Hemisphere migration systems are believed to have arisen since the last glaciation. In many cases, birds do not migrate strait from breeding to non‐breeding areas but fly via a detour. All western European populations of red‐backed shrikes Lanius collurio are assumed to reach their southern African wintering grounds detouring via southeast Europe. Based on theoretical considerations under an optimality framework this detour is apparently optimal. Here, we use individual geolocator data on red‐backed shrikes breeding in Spain to show that these birds do indeed detour via southeast Europe en route to southern Africa where they join other European populations of red‐backed shrikes and return via a similar route in spring. Disregarding potential wind assistance, the routes taken for the tracked birds in autumn were not optimal compared to crossing the barrier directly. For spring migration the situation was quite different with the detour apparently being optimal. However, when considering potential wind assistance estimated total air distances during autumn migration were overall similar and the barrier crossing shorter along the observed routes. We conclude that considering the potential benefit of wind assistance makes the route via southeast Europe likely to be less risky in autumn. However, it cannot be ruled out that other factors, such as following a historical colonisation route could still be important.